Sintesis Karbon Aktif dari Kulit Durian dengan Aktivator HCl dan Aplikasinya sebagai Biosorben Logam Tembaga - Muhsinun Muhsinun (Lembaga Publikasi Ilmiah Nusantara, 2025)
Utilization of biomass waste into activated carbon represents a sustainable strategy for environmental management while also providing eco-friendly functional materials. This study employs durian peel (Durio zibethinus) as the raw material for activated carbon production through carbonization at 400 °C for 2 hours, followed by chemical activation using HCl solution at varying concentrations. The resulting activated carbon was characterized based on its physical properties (moisture content, ash content, iodine adsorption capacity) as well as surface morphology using SEM. Adsorption tests for Cu²⁺ ions were conducted using the batch method under different initial concentrations and contact times. The results showed that HCl activation reduced moisture content to 4.2%, lowered ash content to 3.9%, and enhanced iodine adsorption capacity to 892 mg/g. SEM analysis revealed increased porosity with pore sizes ranging from 0.5–2.5 µm. Adsorption tests indicated an optimum uptake capacity of 40.2 mg/g with efficiency exceeding 80% at a solution concentration of 50 ppm and a contact time of 60 minutes. Adsorption data were better fitted to the Langmuir isotherm model (R² = 0.987) and pseudo-second-order kinetics (R² = 0.991), indicating a monolayer chemisorption-based mechanism. These findings highlight the great potential of durian peel as a low-cost, effective, and environmentally friendly source of activated carbon for the remediation of heavy metal-contaminated wastewater, particularly copper ions.